Collaborative Governance as an Innovative Strategy in Overcoming Stunting in East Flores District - Ibrahim, Siti Noor Khatija; Leus, Jeronimo Da Cruz Neno; Ngatmono, Ngatmono; Dewi, Maya Puspita (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2024)
Despite various intervention programs to address stunting in East Flores Regency, the stunting prevalence rate has not yet reached the target of 10% by 2023. One of the challenges is the lack of community and private sector involvement in handling stunting. In fact, stunting intervention is not only the responsibility of the government, but also requires cross-sector collaboration to work together in optimizing the program. This research discusses collaborative governance as an innovative strategy in overcoming stunting in East Flores Regency. The research method used was qualitative with a descriptive approach. Five health workers and two community development cadres became research informants who were selected purposively. Data analysis used the interactive model of Miles B. Huberman. Data validity was strengthened through triangulation. The results showed that the application of collaborative governance with the penta helix model, namely government, entrepreneurs, academics, civil society, and mass media, is an innovative solution that can be applied in overcoming stunting. The five main stakeholders in the penta helix collaborative governance model can work together synergistically to achieve optimal results in overcoming stunting problems.